Development of a computerised neurocognitive battery for children and adolescents with HIV in Botswana: study design and protocol for the Ntemoga study - Elizabeth D Lowenthal; J Cobb Scott; Amelia E Van Pelt; Allison M Port; Lucky Njokweni; Ruben C Gur; Tyler M Moore; Onkemetse Phoi; Ontibile Tshume; Mogomotsi Matshaba; Kosha Ruparel; Jennifer Chapman (BMJ Open)
Introduction Neurodevelopmental delays and cognitive impairments are common in youth living with HIV. Unfortunately, in resource-limited settings, where HIV infection impacts millions of children, cognitive and neurodevelopmental disorders commonly go undetected because of a lack of appropriate assessment instruments and local expertise. Here, we present a protocol to culturally adapt and validate the Penn Computerized Neurocognitive Battery (PennCNB) and examine its validity for detecting both advanced and subtle neurodevelopmental problems among school-aged children affected by HIV in resource-limited settings.Methods and analysis This is a prospective, observational cohort study. The venue for this study is Gaborone, Botswana, a resource-limited setting with high rates of perinatal exposure to HIV and limited neurocognitive assessment tools and expertise. We aim to validate the PennCNB in this setting by culturally adapting and then administering the adapted version of the battery to 200 HIV-infected, 200 HIV-exposed uninfected and 240 HIV-unexposed uninfected children. A series of analyses will be conducted to examine the reliability and construct validity of the PennCNB in these populations.Ethics and dissemination This project received ethical approval from local and university Institutional Review Boards and involved extensive input from local stakeholders. If successful, the proposed tools will provide practical screening and streamlined, comprehensive assessments that could be implemented in resource-limited settings to identify children with cognitive deficits within programmes focused on the care and treatment of children affected by HIV. The utility of such assessments could also extend beyond children affected by HIV, increasing general access to paediatric cognitive assessments in resource-limited settings.